Sexual Deviations from Islamic Perspective: Sexual Harassment as An Example - Abdulla, Nasih Kareem; Abdalla, Shabaz; Mohammed, Tariq Jabar (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research addresses the pressing global issue of sexual harassment by examining its prevalence and underlying factors. Drawing on international data, our study reveals alarming rates of sexual harassment in various contexts, emphasizing its urgency. Employing a descriptive analysis method, the research investigates the motives and consequences of this behavioral deviation. Findings underscore the roles of education, economics, and the absence of a proper Islamic perspective on sexuality in perpetuating harassment. Educational institutions emerge as pivotal in both occurrence and prevention, while media portrayal of women and insufficient sexual education contribute to societal deviations. The study highlights the multifaceted impact of harassment on mental well-being and advocates for effective punitive measures to curb sexual deviancy and restore social harmony.